운동 목적에 따른 식행동 및 식이섭취 상태 - 신윤진(Yoonjin Shin); 주민정(Minjeong Ju); 김양하(Yangha Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
The aim of this study was to investigate the eating behavior and nutritional status of subjects according to their purpose of exercise. A total of 214 subjects, 20 to 30 years of age, who visited fitness centers in Seoul were enrolled. Anthropometrics, exercise habits, nutritional knowledge, and eating behaviors were analyzed using a questionnaire. Nutritional status was assessed by serial 24 h recalls. The subjects were divided into two groups based on their purpose of exercise: increasing muscle (Muscle growth, n=107) or losing body weight (Weight loss, n=107). The Muscle growth group contained a higher percentage of men, whereas the Weight loss group contained a higher percentage of women. The Muscle growth group showed significantly higher scores of nutritional knowledge and eating behaviors compared to the Weight loss group. The Muscle growth group also had a significantly higher intake of energy and protein compared to the Weight loss group. In fact, the intake of energy in the Weight loss group was lower than the estimated energy requirement (EER) for both men and women subjects. The intake of protein in the Muscle growth group was twice as much as the recommended nutrient intake (RNI). The intake of calcium in both groups was less than the RNI. In conclusion, those who exercised with the aim of increasing muscle took excess dietary protein and those who exercised with the aim of weight loss had a lower energy intake than the EER. 본 연구는 젊은 성인을 대상으로 운동 목적에 따른 영양섭취 실태를 조사하고자 수행되었다. 규칙적으로 운동하고 있는 20~30대 남녀를 대상으로 운동 목적에 따라 근육증가군 107명과 체중감소군 107명을 나누어 비교 분석하였다. 그룹별 성별구성을 분석한 결과, 근육증가군은 주로 남성(75.2%)이 많은 반면 체중감소군은 여성(74.3%)이 많이 분포하고 있었다. BMI 판정결과 두 그룹간의 유의적인 차이는 없었으며, 체중감소군의 절반 이상(56%)이 저체중 또는 정상체중으로 나타났다. 근육증가군의 하루 운동시간 및 규칙적으로 운동한 기간이 체중감소군에 비하여 유의적으로 많았다(p<0.01). 영양지식의 상태는 근육증가군의 점수가 체중 감소군에 비하여 유의적으로 높은 것으로 나타났다(p<0.05). 식행동 또한 근육량 증가군의 점수가 체중감소군에 비하여 유의적으로 높았다(p<0.05). 영양섭취 상태를 살펴보면, 한국인영양섭취기준과 비교하였을 때 근육증가군의 에너지 섭취비율이 에너지필요추정량의 83.72%로 체중감소군의 74.53%에 비하여 유의적로 높았다(p<0.01). 권장섭취량에 대한 단백질 섭취비율은 근육증가군이 199.62%, 체중감소군은 136.36%로 나타났으며 근육증가군이 체중감소군에 비해 유의적으로 매우 많은 양을 섭취하고 있었다(p<0.001). 권장섭취량에 대한 칼슘 섭취비율은 근육증가군이 67.75%, 체중감소군은 68.64%로 조사되었으며, 두 군 모두 권장섭취량과 비교하여 매우 부족한 수준으로 나타났다. 이와 같이 본 연구에서는 근육증가를 목적으로 운동하는 경우 과량의 단백질을 섭취하고 있었으며, 체중감소를 목적으로 운동하는 경우 필요량에 미치지 못하는 에너지 섭취를 하는 것으로 나타났다.